A remarkably air-stable quinodimethane radical cation. Issue 66 (21st July 2020) - Harada, Mei; Tanioka, Masaru; Muranaka, Atsuya; Aoyama, Tetsuya; Kamino, Shinichiro; Uchiyama, Masanobu
Abstract : An ambient-stable radical cation of a Thiele's hydrocarbon derivative has been synthesized and its properties have been explored using a combined experimental and computational approach. Abstract : An ambient-stable radical cation of a Thiele's hydrocarbon derivative has been synthesized and its properties have been explored using a combined experimental and computational approach. The radical cation exhibited several intense near-infrared absorption bands and its solution-processed thin films showed high electrical conductivity at room temperature.